Digital marketing strategy for TMC - Sanvictores, Maribeth C. (University of the Philippines Diliman, 2011)
The digital world has emerged as the result of today's rapid technology advancement. The way people live has changed - the way we communicate, the way we connect with each other, the way we gather information and the way we buy the things we want and need. In turn, digital marketing has also changed the way businesses promote its products and services through the use of different channels such as websites, mobile phones SMS/MMS, display/banner ads and digital outdoor, podcast, voice broadcast, etc. One of the digital channels that have become the faster bridge in doing business and providing services to customers innovatively is the Internet. This in turn paves a new and cheaper way to market in reaching the target customers through implementing internet marketing strategies.